Influence of Permeate from Domestic Reverse Osmosis Filters on Lead Corrosion and Leaching from Plastic Pipes - (:unkn) unknown (My University, 2016)
Reverse Osmosis filters are gaining popularity nowadays, in domestic water supply system, to meet the increasing demand of pure and improved drinking water. There are various types of domestic RO filters with varying sizes, capacities, and treatment stages available. However, there exist a few concerns regarding the RO treatment system. One of the major issues in the quality and distribution of drinking water is the corrosive water that the RO system produces. Therefore, this research herein tends to focus on the corrosive effect of the permeate water on lead metal, as lead is considered a serious problematic drinking water contaminant. In addition, study of the effect of RO product water on leaching of organic carbon from common plastic plumbing materials was also conducted. Three RO filters with varying treatment stages—two-stages, five-stages and seven-stages were chosen for the tests. The lead corrosion was evaluated using immersion corrosion test of lead coupons in water samples for a total of forty days. The two-staged filter showed the highest corrosion effect among the three filters, and the seven-staged filter showed the least. As the number of treatment stages increased, the significant decrease in pH, conductivity, hardness and alkalinity of the water samples also seemed to be less. The overall findings suggested that the impact of number of treatment stages of the filters had a substantial effect on the corrosive property of the water. From the migration test, it was found that the PEX and PVC pipes were prone to organic carbon leaching as compared to the CPVC pipes. The two-staged filter showed the highest extraction of organic compounds in all of the three pipes, and the seven-staged filter showed the least extraction of TOC. In all the samples, including the control, the initial TOC leaching on the third day was higher than the subsequent leaching periods of six and nine days. The leaching of TOC by the RO water samples was hence successfully quantified.
Keywords: Corrosion; Domestic Water Filter; Lead; Organic Carbon Leaching; Plastic Pipe; Reverse Osmosis